Pembangkit Energi Listrik Hybrid Mini Menggunakan Turbin Angin Sumbu Vertikal Savonius Sebagai Sumber Energi Alternatif - Edo Triyandi; Pola Risma; RD Kusumanto; Tresna Dewi; Yurni Oktarina (Journal of Applied Smart Electrical Network and Systems, 2021)
Hybrid system is the concept of combining two or more different energy sources to meet the needs of the existing electrical load, so this is expected to overcome energy use if the supply of other electrical energy is problematic. One example is the merging of solar energy and wind energy. The advantages of this hybrid generator are that it is non-polluting, abundant, never runs out and can be used directly or indirectly and is energy for all time. In the wind energy generator section, the type of Savonius vertical axis wind turbine is used, where this turbine is very suitable for use in low-speed wind types such as the one in the city of Palembang using the MY-1016 generator with an output power of 350 Watt. The mini hybrid electric energy generation system uses a savonius vertical axis wind turbine as an alternative energy source consisting of several components, including: Savonius vertical axis wind turbine, MY-1016 Generator, Controller, Internet of Things (IOT), Anemometer sensor, INA219 current sensor, Energy storage system (battery, pump storage), and 1500-Watt Inverter.